Conductometric and potentiometric determination of the solubility products of some distigmine ion recognition species - Issa, Y. M.; El Ries, M. A.; Khorshid, A. (Univerzita Pardubice, 2010)
A conductometric method is proposed to determine the sparingly soluble ion-associate of Distigmine. A comparison between conductometric and ISEs values has shown that the conductometric method is suitable, rapid, and easy-to-perform. The Distigmine-ISE is successfully used for the determination of solubility products of different sparingly soluble salts of Distigmine of the Ds3PM2, Ds3PT2, Ds2SM, Ds2ST, DsTPB2, DsRein2 and DsPi2 stoichiometry. The solubility products determined by Ds-ISE were found to be in good agreement with the values obtained by conductometric method. Finally, the solubility products for Ds3PM2, Ds3PT2, Ds2SM, Ds2ST, DsTPB2, DsRein2, and DsPi2 were found to be 4.92×10-25, 5.61×10-25, 2.27×10-28, 4.71×10-28, 3.11×10-14, 5.91×10-15, and 6.40×10-14, respectively.
Keywords: potentiometry and conductometry; ion-selective electrodes; distigmine; sparingly soluble salts; solubility products